KAJIAN TEOLOGIS FEMINIS KEPEMIMPINAN DEBORA SEBAGAI PEREMPUAN YANG TEGAS MENURUT KITAB HAKIM-HAKIM 4-5 - Rutwansari Miranti Rara’; Andreas Satti; Risma Yulius (Adisam Publisher, 2026)
On this occasion I am a journal writer with the aim of fulfilling the assignment given to me as a student with the title of a feminist theological study of Debora's leadership as a firm woman according to the book of judges 4-5. Here we know that not all women can always be considered weak or unable to do anything. But again we realize that God created us in the image and likeness of God. So nothing is impossible if God is dealing with things in our lives like in temples that have a female gender, and we know that women always get a different or different opinion than a man, which is nothing new for us to hear that someone men become leaders. Gender news, the position of men is always used as a benchmark that they are at best special compared to a woman. This opinion or story causes misunderstandings to occur between women and men, including in the world of Christian theology, so this is what always happens, some even forbid or do not allow a woman's position to be a leader above men, and some even always based on gender whether he is the gender of a woman or a man and of course a man who does not need to be questioned whether he can be a leader or not. So through this assignment, I, as a writer, have the curiosity to find out what parts of the book are found in Judges 4-5, use methods so that I can know and understand that the characteristics of a leader's gender are not always seen in gender and not based on gender. may choose one gender but must be able to choose a leader who is obedient before God, and can be an example or role model for everyone around him and wherever he is he can reflect the qualities of God.